Sufism in the Digital Age: The Relevance of Maqamat wa Ahwal in Addressing the Spiritual Crisis of Modern Muslims - Cici Nurmianty (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to comprehensively describe Sufism in the digital era: The Relevance of Maqamat Wa Ahwal in addressing the spiritual crisis of modern Muslims. This study uses a qualitative method with a library research approach through searching various documents, in the form of books, scientific journals, academic articles, and other scientific works that discuss the concept of maqam and ahwal in Sufism. The results of this study indicate that maqamat is a spiritual position or stage achieved through mujahadah and riyadhah which must be passed through stages, while ahwal is a condition or characteristic that is never attempted, but is purely a gift from Allah. Maqamat and Ahwal are very relevant in answering the spiritual crisis of modern Muslims by using the maqam (stages) Al-taubah, Al-Zuhud, Al-Wara, Al-faqr, Al-shabr, Al-tawakkal and Al-ridha and ahwal which have parts including Al-muraqabah, Al-khauf, Al-raja’, Al-syauq, Al-Uns, Al-Thuma’ninah, Al-Musyahadah, and Al-yaqin. These concepts will be a guideline for humanity to achieve true closeness to Allah SWT even though Muslims are often distracted by modern life.